해양생물 다양성 연구를 위한 환경유전자(eDNA)의 적용 - 최소윤; 이승재; 최은경; 조은아; 김진무; 조민주; 김장연; 권수연; 박현; Soyun Choi; Seung Jae Lee; Eunkyung Choi; et al. (한국해양생명과학회지, 2023)
eDNA, an abbreviation for environmental DNA, means DNA derived from organisms inhabiting in a specific environment. The utilization of eDNA extracted from environmental samples allows for efficient and accurate monitoring of organisms inhabiting the respective environment. Specifically, eDNA obtained from seawater samples can be used to analyze marine biodiversity. After collecting seawater samples and extracting eDNA, metagenome analysis enables the taxonomic and diversity analysis among marine organisms inhabiting the sampled area. This review proposed an overall process of marine biodiversity analysis by utilizing eDNA from seawater. Currently, the application of eDNA for analyzing marine biodiversity in domestic setting is not yet widespread. This review can contribute to establishment of marine eDNA research methods in Korea, providing valuable assistance in standardizing the use of eDNA in marine biodiversity studies. eDNA (environmental DNA)란 특정 환경에 서식하는 생물로부터 유래한 DNA를 의미한다. 환경 시료로부터 추출한 eDNA를 활용하면 해당 환경에 서식하는 생물들의 효율적이고 정확한 모니터링을 수행할 수 있다. 해수 시료로부터 얻은 eDNA를 기반으로 해양생물 다양성 연구를 수행할 수 있다. 해수 시료를 채집하고 이로부터 eDNA를 추출한 뒤, metagenome 분석을 통해 서식하는 해양생물의 종 동정과 다양성 분석이 가능하다. 본 리뷰에서는 이처럼 해수의 eDNA를 활용하여 해양 지역의 생물 다양성 연구를 수행하는 전체적인 과정을 제시하고 있다. 아직 국내에는 해양생물 다양성 연구를 위해 eDNA를 적용하는 방법이 보편화 되어있지 않으며, 본 리뷰를 기반으로 이와 같은 eDNA 연구 방법을 정립하는데 도움을 줄 수 있을 것이다.